ANALISIS FAKTOR PENYEBAB PERILAKU PELECEHAN SEKSUAL TERHADAP ANAK DI BAWAH UMUR DI KECAMATAN ANGATA KABUPATEN KONAWE SELATAN - Sitti Dahlia; Sartiah Yusran; Ramadhan Tosepu (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Sexual behavior is a serious problem in developed and developing countries. In the world, an average of 35.6% or 1 in 3 people have had a sexual experience. The high number indicates that sexual behavior is still commonplace. The purpose of this study was to analyze the factors causing sexual behavior towards minors in Angata District, Konawe Selatan Regency in 2021. The design of this study was a qualitative research using a phenomenological approach that produced descriptive data. The data obtained from the results of in-depth interviews and observations were then analyzed using the content analysis method. Based on the results of the study showed that the perpetrators did not have good knowledge with low educational backgrounds. The perpetrator has a positive attitude towards the action taken, so that the perpetrator wants to take action after experiencing an increase in sexual desire. Perpetrators have an easy attitude to follow a friend's invitation to take open actions. However, there is a sense of regret and will not repeat the attitude and behavior. It is reasonable to take action when you see minors or the opposite sex, but it will be difficult to control your actions when you have sexual urges, coupled with the influence of drinking, as well as opportunities and opportunities. The circle of friends of the perpetrators who often do negative things so that many of their friends in the environment become perpetrators and also victims. Things that are often done with friends in the perpetrator's environment are gathering until the early hours of the morning doing liquor, and watching pornographic videos, etc. Some of the perpetrators were educated quite hard and some were educated appropriately, such as being sent to school, although many of the perpetrators dropped out of school. Interaction of family members is very rare because of their busy lives.